Perlindungan Hukum Pekerja Penyandang Cacat Menurut Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Ramadhan, Muhammad Fadli (Lentera Hukum, 2015)
The understanding of the community for people with whom diffability has always been considered an inability someone physically so that diffability regarded as sick people who always need help and comfort to the aid for both in terms of their education as well as a job. Now the condition is changed in the priesthood there any intervention from the government that very glows amber metal out of the field of labor affairs so that this superior wisdom whose is issued by a government but how much broad, not only legal aspects that deals with a working relationship and calm but before and after a working relationship. This concept in an obscure manner accommodated in act number 13 the year 2003 on manpower regarding. Diffability must be viewed as a social inability that anyone can participate to protect the minorities, of course, the social approach is the main road that could be pursued. Here is required legal protection for diffability people so that diffability people can find a legal certainty that rights for a people with the diffability KEYWORDS: Legal Protection, Workers, People with Dasabilities.